Coexistent Coronary Artery Disease in Patients Undergoing Permanent Pacemaker Implantation - A Study from Major Center in North Eastern India - Bornali Dutta (Journal of Clinical and Preventive Cardiology)
Aim: Data regarding the incidence of coexisting coronary artery disease (CAD) in patients undergoing permanent pacemaker implantation (PPI) in our country are limited. The incidence of coexisting CAD and its clinical characteristic in patients undergoing PPI have not been reported from North-east India. This study has been undertaken to study the incidence of coexisting CAD in patients undergoing PPI with risk factors for CAD or with documented atherosclerotic cardiovascular disease (ASCVD) and also to compare the clinical characteristics between patients with and without CAD.